Comprehensive profiling of pre-infection antibodies identifies HIV targets associated with viremic control and viral load - Grant-McAuley, Wendy; Morgenlander, William; Hudelson, Sarah E.; Thakar, Manjusha; Piwowar-Manning, Estelle; Clarke, William; Breaud, Autumn; Blankson, Joel; Wilson, Ethan; Ayles, Helen; Bock, Peter; Moore, Ayana; et al. (Frontiers in Immunology, 2023)
High HIV viral load (VL) is associated with increased transmission risk and faster disease progression. HIV controllers achieve viral suppression without antiretroviral (ARV) treatment. We evaluated viremic control in a community-randomized trial with >48,000 participants. A massively multiplexed antibody profiling system, VirScan, was used to quantify pre-and post-infection antibody reactivity to HIV peptides in 664 samples from 429 participants (13 controllers, 135 viremic non-controllers, 64 other non-controllers, 217 uninfected persons). Controllers had VLs <2,000 copies/mL with no ARV drugs detected at the first HIV-positive visit and one year later. Viremic non-controllers had VLs ≥2,000 copies/mL with no ARV drugs detected at the first HIV-positive visit. Other non-controllers had either ARV drugs detected at the first HIV-positive visit (n=47) or VLs <2,000 copies/mL with no ARV drugs detected at only one HIV-positive visit (n=17). We identified pre-infection HIV antibody reactivities that correlated with post-infection VL. Preinfection reactivity to an epitope in the HR2 domain of gp41 was associated with controller status and lower VL. Pre-infection reactivity to an epitope in the C2 domain of gp120 was associated with non-controller status and higher VL. Different patterns of antibody reactivity were observed over time for these two epitopes. These studies suggest that pre-infection HIV antibodies are associated with controller status and modulation of HIV VL. These findings may inform research on antibody-based interventions for HIV treatment.